2D covalent organic framework thin films via interfacial self-polycondensation of an A2B2 type monomer. Issue 22 (4th March 2020) - Zhang, Bowen; Song, Xiaoyu; Li, Yusen; Li, Yang; Peng, Zhongxiang; Ye, Long; Chen, Long
Abstract : Highly crystalline and oriented 2D Py-COF thin films were readily fabricated via an elaborately designed A2 B2 monomer, and served as stable acidichromism sensors with rapid response, low detection limit and good repeatability. Abstract : An A2 B2 type monomer, 1, 6-bis(4-formylphenyl)-3, 8-bis(4-aminophenyl)pyrene (BFBAPy), was employed for the fabrication of continuous and highly crystalline 2D imine-linked covalent organic framework (COF) films with tunable thickness via interfacial self-polymerization. These films served as stable acidichromism sensors with rapid response, low detection limit and good repeatability.